Impact of COVID-19 Infection on Regional Periocoronary Inflammation: An Angio-CT Study of Epicardial Fat Attenuation - Mátyás Botond; Benedek Imre; Opincariu Diana; Blîndu Emanuel; Rosea Aurelian; Rodean loana; Benedek Bianka; Benedek Theodora (Sciendo, 2023)
It is currently well-known that inflammation plays an essential role in all phases of atherosclerosis. Recent CT studies showed that atherosclerotic plaques found in the right coronary arteries (RCA) display a greater number of features that increase their susceptibility to destabilization compared to plaques found in left coronary arteries (LCA). COVID-19's impact on regional coronary inflammation is not well understood, despite extensive research on its effects on cardiovascular diseases.